Improving Students’ Critical and Creative Thinking through Realistic Mathematics Education using Geometer’s Sketchpad - Dhayanti, Decy; Johar, Rahmah; Zubainur, Cut Morina (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2018)
Learning can foster students’ character as well as their understanding. Realistic Mathematics Education (RME) is one of learning approach to foster those competences. In this research, the learningbased RME will be supported by using the Geometer's Sketchpad. This study aims to improve the students’ character through Realistic Mathematics Education using Geometer's Sketchpad on proportion topic and analyze the student's learning achievement . The subjects of this research are the 25 eighth grade students in one of public secondary school in Aceh Tamiang, Aceh. Instruments used in the study are character observation sheets and test to assess students’ learning achievement. The data analysis technique used is descriptive analysis. The result of data analysis shows that the implementation of Realistic Mathematics Education using Geometer's Sketchpad in topic of proportion can improve student's critical and creative thinking. In addition student's learning achievement met the minimal mastery criteria.